Modellierung und Ausführung von Workflows unter Berücksichtigung mobiler Kontextinformationen - Stürzel, Peter (KIT Scientific Publishing, 2018)
Existing business modeling languages (or their extensions) have time, identity and activity related contexts (or objects) for modeling business processes. In order to support a Context Aware Service, location awareness is needed to enable the application or process to control the related workflows. For the integration of location constraints into workflow models, a concept based on restrictions is being developed in the present work.